Subtype-Based Analysis of Cell-in-Cell Structures in Esophageal Squamous Cell Carcinoma - Wang, Yuqi; Niu, Zubiao; Zhou, Lulin; Zhou, Yongan; Ma, Qunfeng; Zhu, Yichao; Liu, Mengzhe; Shi, Yinan; Tai, Yanhong; Shao, Qiuju; Ge, Jianlin; Hua, Jilei; et al. (Frontiers in Oncology, 2021)
Cell-in-cell structures (CICs) are defined as the special structures with one or more cells enclosed inside another one. Increasing data indicated that CICs were functional surrogates of complicated cell behaviors and prognosis predictor in heterogeneous cancers. However, the CIC profiling and its prognostic value have not been reported in human Esophageal Squamous Cell Carcinoma (ESCC). We conducted the analysis of subtyped CIC-based profiling in ESCC using “Epithelium-Macrophage-Leukocyte” (EML) multiplex staining and examined the prognostic value of CICs profiling through Kaplan-Meier plotting and Cox regression model. Totally, five CIC subtypes were identified in ESCC tissue and the majority of them was homotypic CIC (hoCIC) with tumor cells inside tumor cells (TiT). By univariate and multivariate analysis, TiT was shown to be an independent prognostic factor for rescetable ESCC and patients with higher density of TiT tended to have longer post-operational survival time. Furthermore, in subpopulation analysis stratified by TNM stage, high TiT density was associated with longer overall survival (OS) in patients of TNM stage III and IV as compared with patients with low TiT density (mean OS: 51 vs 15 months, P=0.04) and T3 stage (mean OS: 57 vs 17 months, P=0.024). Together, we reported the first CIC profiling in ESCC and explored the prognostic value of subtyped CICs, which supported the notion that functional pathology with CIC profiling is an emerging prognostic factor for human cancers such as ESCC.